Pengaruh Kedisiplinan, Pelatihan Kerja, dan Gaya Kepemimpinan Terhadap Produktivitas Karyawan PT Yuna Mandiri Plosokandang Tulungagung - Bima Dyatmika Widigda; Karari Budi Prasasti; Nuril Aulia Munawaroh (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine the influence of discipline, job training, and leadership style on employee productivity at PT Yuna Mandiri Plosokandang Tulungagung. In a competitive world of work, employee productivity is an important indicator in assessing company performance. This study uses a quantitative method with a descriptive approach. The sample used was all permanent employees of PT Yuna Mandiri totaling 38 people, with a non-probability sampling technique with a saturated sampling method. The data collection technique was carried out through the distribution of questionnaires, then analyzed using validity, reliability, multiple linear regression tests, t-tests, F tests, and determination coefficients (R²) using SPSS software. The results of the study show that 1) discipline partially has no effect on employee productivity, 2) job training partially affects and significantly affects employee productivity, 3) leadership style partially has no effect on employee productivity, 4) discipline, job training, and leadership style simultaneously have an effect and significant on employee productivity. Thus, increasing employee productivity in the company can be done through efforts to strengthen work discipline, provide targeted job training, and implement an effective leadership style.